The Main Trends in the Development of the Process of Training Future Primary School Teachers in Higher Education - Keldiyorova Manzura Gaybullayevna (Zien Journals, 2022)
The article focuses on the fundamental principles, systematization of updating the content of primary education, which has become an urgent problem and requirement for the development of the system of continuous professional pedagogical education, increasing the level of professional pedagogical training of primary school teachers. based on the integrity, consistency and practice-oriented, the main trends and necessary factors in the development of the process of training future primary school teachers in higher education, as well as competitive in the process of higher education, able to quickly adapt to new conditions, the issue of formation of a modern specialist who can work effectively in the labor market at the level of the requirements for the qualification of specialists is analyzed
Keywords: education; student; qualification; specialist